Impact of Social Network Sites on Developing Brand Communication in Xian City - Yiming Zhang; Lai, Che Ghing (IJCNIS Journal - UK Zhende Publishing, 2023)
The digital era mobilises the world cities with various traits and symbolic resources to brand the images of the cities through propagation in social media (SM) platforms. This work examines Xian, the fastest developing city in China, which is in the process of building its brand through SM platforms. The model proposed in this work uses elaborative variables that are categorized into four indicators which characterizes the behaviours of users in the SM. Each variable is weighted based on the entropy method each one has a varied level of intensity in the model. The detailed results indicate that the size of the network is a significant factor in construction of brand communication through the SM platforms. Further, the study also includes the descriptive statistics and correlation analysis of individual explanatory variables with the model’s output value. The result of this analysis indicates that connections with friends and a number of followers as crucial factors in board communication of Xian city. This work can guide the local municipal authorities to advertise and influence SM users to create a positive brand of the city.